Influence of Season on the Microbial Quality of Fresh and Processed Prawn - Iyer, T. S. Gopalakrishna; Chaudhuri, D. R.; Pillai, V. K. (Fishery Technology, 1970)
The present communication deals with the influence of season on the microbial quality of fresh prawn handled under tropical conditions as obtained in India. Warmer months favour multiplication of bacteria including faecal streptococci, whereas high incidence of E. coli during rainy seasons is probably due to high degree of faecal pollution of water during the period. As seen from the foregoing study, higher bacterial counts in certain specific seasons’ emphasise the necessity for stricter sanitary codes to maintain a uniform minimum bacterial standard for the processed fishery products.